1983
DOI: 10.1111/j.1600-0528.1983.tb01350.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal treatment need of the Finnish population aged 30 years and over

Abstract: A representative sample (n = 8000) was drawn from the population aged 30 years and over, registered as living in Finland. Periodontal disease status was recorded according to the modified Periodontal Treatment Need System (PTNS). Plaque retentions were examined separately. Of the subjects with four or more teeth 3.4% had a healthy periodontal status, while 10.2% of the jaw quadrants were healthy. Plaque retentions were found in 96.6% of the subjects and 90.9% of the jaw segments. Periodontal treatment need was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
2
9

Year Published

1985
1985
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 16 publications
4
16
2
9
Order By: Relevance
“…Interview data were obtained for 96.5% of the random sample. Details of the sampling procedure and of the survey have been described previously (Markkanen, 1982;Markkanen et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Interview data were obtained for 96.5% of the random sample. Details of the sampling procedure and of the survey have been described previously (Markkanen, 1982;Markkanen et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…In their study, Markkanen and co-workers showed that the age of the patient is a significant factor for periodontal treatment need (8). According to a Swedish study (9), multiple periapical lesions were more usual in the age group 75 years and older than in the group 65±74 years.…”
mentioning
confidence: 96%
“…The number of sites with significant bone loss as well as the rate of bone loss increases steadily over time (7,8). In their study, Markkanen and co-workers showed that the age of the patient is a significant factor for periodontal treatment need (8).…”
mentioning
confidence: 99%
“…The indicators used to describe periodontal conditions were presence or absence of gingival inflammation or periodontal pockets and subgingival plaque retentions (calculi and/or overhang ings). Based upon the PTNS index [Johansen et al, 1973;Markkanen et al, 1983], the state of the periodontium was first placed in 1 o f 4 cat egories: 1 = healthy; 2 = gingival inflammation; 3 = pockets 4-6 mm deep, and 4 = pockets > 6 mm deep. In further analyses, the severity of periodontal disease was described according to presence and depth of pockets, using these three categories: 1 = no deepened pockets; 2 = pockets 4-6 mm deep, and 3 = pockets > 6 mm deep.…”
mentioning
confidence: 99%